University Student Equity Initiatives: An Examination of the Efficacy of Programs and Practices to Inform Best Practice - de Vries, Jennifer Carol (Curtin University, 2018)
This thesis identifies “Indicators of Success” for university student equity programs funded through the Higher Education Participation and Partnerships Program (HEPPP). This research focussed on practitioner perspectives of evaluation and reporting practices for equity programs which seek to widen participation in higher education by disadvantaged groups within the community. This research has produced an “Indicators of Success” framework and good practice model, at a time of heightened discussion about the evaluation of HEPPP funded programs.